Detecting adventitious transgenic events in a maize center of diversity - Rimachi Gamarra, Luis Fernando; Alcántara Delgado, Jorge Enrique; Aquino Villasante, Yeny Natali; Ortiz Rios, Rodomiro Octavio (Pontificia Universidad Católica de Valparaíso, 2020)
Background: The genetic diversity of maize in Peru includes several landraces (within race clusters) and modern open pollinated and hybrid cultivars that are grown by farmers across various regions, thereby making this country a secondary center of diversity for this crop. A main topic of controversy in recent years refers to the unintended presence of transgenic events in locally grown cultivars at main centers of crop diversity. Peru does not yet have biosafety regulations to control or permit the growing of genetically modified crops. Hence, the aim of this research was to undertake a survey in the valley of Barranca, where there were recent claims of authorized transgenic maize grown in farmers fields as well as in samples taken from feed storage and grain or seed trade centers. Results: A total of 162 maize samples (134 from fields, 15 from local markets, eight from the collecting centers of poultry companies, from the local trading center and four samples from seed markets) were included for a qualitative detection by the polymerase chain reaction (PCR) of Cauliflower Mosaic Virus (CaMV) 35S promoter (P35S) and nopaline synthase terminator (Tnos) sequences, as well as for six transgenic events, namely BT11, NK603, T25, 176, TC1507 and MON810. The 134 maize samples from farmers fields were negative for Cry1Ab delta-endotoxin insecticidal protein and enzyme 5 enolpyruvylshikimate-3-phosphate synthase (EPSPS) using lateral flow strips. The PCR analysis did not detect any of the six transgenic events in samples from farmers fields, local markets, seed trading shops and the local collecting center. There were four transgenic events (T25, NK603, MON810 and TC1507) in grain samples from the barns of poultry companies. Conclusions: This research could not detect, at the 95% probability level, transgenes in farmers' fields in the valley of Barranca. The four transgenic events in grain samples from barns of poultry companies were not surprising because Peru imports maize, mainly for animal feed, from Argentina and the United States that are known for growing transgenic maize.